Short- and long-term prognosis of patients with community-acquired Legionella or pneumococcal pneumonia diagnosed by urinary antigen testing - Leyre Serrano; Luis Alberto Ruiz; Silvia Perez-Fernandez; Pedro Pablo España; Ainhoa Gomez; Beatriz Gonzalez; Ane Uranga; Sonia Castro; Milagros Iriberri; Rafael Zalacain (International Journal of Infectious Diseases, 2023)
Objectives: To analyze the differences in short- and long-term prognosis and the predictors of survival between patients with community-acquired Legionella and Streptococcus pneumoniae pneumonia, diagnosed early by urinary antigen testing (UAT). Methods: Prospective multicenter study conducted in immunocompetent patients hospitalized with community-acquired Legionella or pneumococcal pneumonia (L-CAP or P-CAP) between 2002-2020. All cases were diagnosed based on positive UAT. Results: We included 1452 patients, 260 with community-acquired Legionella pneumonia (L-CAP) and 1192 with community-acquired pneumococcal pneumonia (P-CAP). The 30-day mortality was higher for L-CAP (6.2%) than for P-CAP (5%). After discharge and during the median follow-up durations of 11.4 and 8.43 years, 32.4% and 47.9% of patients with L-CAP and P-CAP died, and 82.3% and 97.4% died earlier than expected, respectively. The independent risk factors for shorter long-term survival were age >65 years, chronic obstructive pulmonary disease, cardiac arrhythmia, and congestive heart failure in L-CAP and the same first three factors plus nursing home residence, cancer, diabetes mellitus, cerebrovascular disease, altered mental status, blood urea nitrogen ≥30 mg/dl, and congestive heart failure as a cardiac complication during hospitalization in P-CAP. Conclusion: In patients diagnosed early by UAT, the long-term survival after L-CAP or P-CAP was shorter (particularly after P-CAP) than expected, and this shorter survival was mainly associated with age and comorbidities.